Palaeomagnetism of Mesozoic magmatic bodies of the Fuegian Cordillera: implications for the formation of the Patagonian Orocline - Rapalini, Augusto Ernesto (2015)
It is not known whether the Patagonian Orocline, the major bend of the southern Andes at the southern tip of South America, is a primary or secondary feature. Palaeomagnetic data along the Patagonian Orocline are still too scarce to provide a reliable and unambiguous answer to this question. New palaeomagnetic results on Late Jurassic–Late Cretaceous magmatic units along the central segment of the Fuegian Cordillera are reported. Data from four Late Cretaceous small intrusions and three sites on Late Jurassic–Early Cretaceous metabasalts and metagabbros showed anticlockwise declination deviations between 218 and 468 with respect to South America. From these and previous data, a picture of a nearly homogeneous post-Late Cretaceous regional rotation of the central Fuegian Cordillera is suggested. This supports a model of nearly 308 of anticlockwise secondary bending of the Patagonian Orocline since the Late Cretaceous (72 Ma). Lack of rotation of post-50 Ma sedimentary rocks exposed to the north of our study region, and larger rotations (of c. 908) reported to the south of it suggest that a geographical and/or temporal progression of rotation values from south to north in the Fuegian part of the Patagonian Orocline should be investigated.